A novel bladder cancer surveillance schedule using bladder Cx for patients on annual surveillance - Arjun Guduguntla; Thomas Whish‐Wilson; Lauren Chandler; Dennis Gyomber (BJUI Compass)
Abstract Objectives Cx bladder monitor (CxM) is a urine test with a proven high sensitivity and negative predictive value in bladder cancer surveillance. The aim of this retrospective study was to report on the outcomes of our newly implemented bladder cancer surveillance program for patients eligible for yearly cystoscopy, as per the European Association of Urology (EAU) guidelines. In this program, eligible patients alternate between yearly surveillance cystoscopy and CxM, instead of the standard yearly surveillance cystoscopy. Outcomes measures were overall results of CxM and subsequent treatment patterns of patients, impact on waiting lists, cost comparison and patient satisfaction. Patients and Methods In 2022, 109 eligible and consenting patients were identified, with 98 commencing on the new surveillance program, starting with CxM instead of cystoscopy. A negative CxM, would result in a planned flexible cystoscopy in 12 months. If a patient had a positive CxM, they proceeded to undergo a cystoscopy, and if required, imaging. Results Of the 98 that underwent testing, 90 had a negative CxM test and 8 patients had a positive CxM test. Three of these eight were true positive (PPV 0.375). Seventy negative CxM patients had no recurrence at the time of the next cystoscopy/imaging. Of the remaining 20 negative CxM patients, 11 were found to have a recurrence at subsequent cystoscopy/imaging and 9 did not proceed with further surveillance for various reasons. All of the tumour recurrences diagnosed after a negative CxM were non‐invasive, thus there was no progression to muscle‐invasive disease. All suitable patients consented to continuing with the CxM protocol. The hospital surveillance cystoscopy waitlist was reduced by approximately 59% and CxM was approximately $850 AUD cheaper than a cystoscopy. Conclusion CxM can be safely used in an alternating schedule with Flexible Cystoscopy for patients on annual bladder cancer surveillance.